(untitled) (Journal of Human Sciences, 2023)
All over the world, Covid-19 pandemic made all the educational institutions suddenly shift to online learning. Google Classroom is one of the most online learning platform used by teachers and students during this period of time, as it is one of the most popular Learning Management Systems (LMS). Google Classroom was chosen by Sebha University to provide teachers and students with online learning materials, assignments, projects, and tests. This research aims to share the learning experience of foreign English Language students in online learning using Google Classroom application as a learning platform. Along with the role that played by Google Classroom to improve their English Language in listening, speaking, writing, and reading skills. The respondents were limited to 25 students enrolled in the research methodology class in a collage of Education of Sebha university in Zawila during the sixth, seventh and eighth semesters of the school year 2021-2022. It was concluded that learning English by using Google Classroom gives a number of advantages for students. The advantages is easy to operate, flexible time of teaching and learning, and supporting various learning sources. However, the results also shows that Google Classroom has disadvantages, it is not running effectively and efficiently as expected to improve all their four language skills. As well as they had some difficulties in terms of the ease of access due to the lack of facilities experienced and the internet connection speed problems so the majority of the students had got a number of problems using Google Classroom. The study suggests that the students must adapt to these circumstances in case to avoid any similar situation, therefor the university should offer courses for the students who they must be aware of technology to use it in the learning process to get all benefits of such application.